2018
DOI: 10.1155/2018/8923028
|View full text |Cite
|
Sign up to set email alerts
|

Fully Automated Delineation of Gross Tumor Volume for Head and Neck Cancer on PET-CT Using Deep Learning: A Dual-Center Study

Abstract: Purpose In this study, we proposed an automated deep learning (DL) method for head and neck cancer (HNC) gross tumor volume (GTV) contouring on positron emission tomography-computed tomography (PET-CT) images. Materials and Methods PET-CT images were collected from 22 newly diagnosed HNC patients, of whom 17 (Database 1) and 5 (Database 2) were from two centers, respectively. An oncologist and a radiologist decided the gold standard of GTV manually by consensus. We developed a deep convolutional neural network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 28 publications
0
74
0
Order By: Relevance
“…This level of performance was obtained on eyes to thighs datasets where overall lesion burden is sparse and anatomical background is highly heterogeneous. Previous published work ( [22,23], with DSC of 0.732 and 0.85, respectively) was based on more limited, less sparse, and more homogeneous regional scans.…”
Section: Resultsmentioning
confidence: 99%
“…This level of performance was obtained on eyes to thighs datasets where overall lesion burden is sparse and anatomical background is highly heterogeneous. Previous published work ( [22,23], with DSC of 0.732 and 0.85, respectively) was based on more limited, less sparse, and more homogeneous regional scans.…”
Section: Resultsmentioning
confidence: 99%
“…Automatic nasopharyngeal carcinoma tumor segmentation from 18 F-FDG PET/CT scans using a U-Net architecture proved the feasibility of this task (dice coefficient = 0.87) using AI-based algorithms (Zhao et al 2019a). Similar studies on head and neck (Huang et al 2018), as well as lung cancers (Zhao et al 2018) exhibited promising results using convolutional neural networks for automated tumor segmentation from PET/CT images. Nevertheless, fully automated lesion delineation from PET, CT, and MR images or any combination of these images still remains a major challenge owing to the large variability of lesion shape and uptake associated with various malignant diseases.…”
Section: Image Segmentationmentioning
confidence: 78%
“…Zhao et al showed, for a small group of 30 patients, that the automatic segmentation of such tumors on 18 F-FDG PET/CT data was, in principle, possible using the U-Net architecture (mean Dice score of 87.47%) (44). Other groups applied similar approaches to head and neck cancer (45) and lung cancer (46,47). Still, fully automated tumor segmentation remains a challenge, probably because of the extremely diverse appearance of these diseases.…”
Section: Discussionmentioning
confidence: 99%